Avaliação da maturidade em gestão de processos em um setor de um Instituto Federal de Educação usando o modelo PEMM - Fontes, Daniela Amorim (Universidade Federal de São Carlos, 2024)
Business process management (BPM) makes it possible to achieve better results for organizations. By assessing BPM maturity, it is possible to identify gaps and direct actions to improve organizations' processes. The present work aims to evaluate the degree of maturity in the management of academic records processes at a Federal Institute of Education, more precisely in the Academic Records Coordinations – CRAs sector. This sector is responsible for the documentation of the institution's students during their academic career. It operates in the execution of many processes, involving a wide variety of regulations. To achieve the intended objectives, the work was developed based on applied, exploratory, qualitative research, using bibliographic review and case study techniques. To assess maturity, the Process and Enterprise Maturity Model (PEMM) model was chosen, applicable in a single sector and in public institutions, which generates as a result indicators of actions to advance the maturity level. The model has two data collection instruments and one of the instruments was used for this work. The model's own collection instrument was applied to the sector's servers, resulting in a maturity level of P0, demonstrating that the sector's processes have not yet reached a reliable and predictable form and that they function irregularly. Despite the existence of indicators of development of process management, the organization does not focus on the development of its business processes. The results obtained demonstrate that the institution needs to focus efforts on the development of its processes, seeking to advance the design of each process, provide training for its executors, define those responsible for its processes, invest in an integrated system to support the processes and define indicators and use them to improve performance. As a suggestion for future studies, the application of the two instruments of the model in an organization is highlighted.
Assessment of maturity in process management in a sector of a federal institute of education using the PEMM model
Keywords: Modelo de maturidade; Gestão de processos; Organização pública; PEMM; Maturity model; Business Process Management (BPM); Public organization; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO